Effect of vacuum frying process on the quality of a snack of mango (manguifera indica l.) (2012)
The latest trends in consumption of snacks, have led to the search for processes that enhance the quality of snack. The aim of this study was to observe the behavior of quality parameters of a fried snack made from mango (Manguifera indica L.), using vacuum on a base of mango pulp and starch, in their preparation. The frying process was carried out using different vacuum pressures (0.4, 0.5, 0.6 bar), temperatures (100, 110 and 120 ° C) and times (30, 45, 60, 75 and 90s.) The results showed that the vacuum improves the quality characteristics of the snacks, finding a fat and very low humidity contents, lower water activity, and texture, according to market products and a small color variation with respect to paste color. The best treatment was to 0.5 bar, 110 ºC y 90s of immersion time.